Astrocyte 3D culture and bioprinting using peptide functionalized hyaluronan hydrogels. Issue 1 (31st December 2023) - Matthiesen, Isabelle; Jury, Michael; Rasti Boroojeni, Fatemeh; Ludwig, Saskia L.; Holzreuter, Muriel; Buchmann, Sebastian; Åman Träger, Andrea; Selegård, Robert; Winkler, Thomas E.; Aili, Daniel; Herland, Anna
ABSTRACT: Astrocytes play an important role in the central nervous system, contributing to the development of and maintenance of synapses, recycling of neurotransmitters, and the integrity and function of the blood–brain barrier. Astrocytes are also linked to the pathophysiology of various neurodegenerative diseases. Astrocyte function and organization are tightly regulated by interactions mediated by the extracellular matrix (ECM). Engineered hydrogels can mimic key aspects of the ECM and can allow for systematic studies of ECM-related factors that govern astrocyte behaviour. In this study, we explore the interactions between neuroblastoma (SH-SY5Y) and glioblastoma (U87) cell lines and human fetal primary astrocytes (FPA) with a modular hyaluronan-based hydrogel system. Morphological analysis reveals that FPA have a higher degree of interactions with the hyaluronan-based gels compared to the cell lines. This interaction is enhanced by conjugation of cell-adhesion peptides (cRGD and IKVAV) to the hyaluronan backbone. These effects are retained and pronounced in 3D bioprinted structures. Bioprinted FPA using cRGD functionalized hyaluronan show extensive and defined protrusions and multiple connections between neighboring cells. Possibilities to tailor and optimize astrocyte-compatible ECM-mimicking hydrogels that can be processed by means of additive biofabrication can facilitate the development of advanced tissue and disease models of the central nervous system. Graphical abstract: uf0001